Analyzing the impact of agricultural drought on meteorological drought within Pakistan’s Upper Indus, Kabul, and Jhelum River Basins - Chang, J.; Hussain, A.; Kai, Z.; Yang, G.; Zhang, L. (2025)
Pakistan has experienced unpredictable drought conditions in recent years which affected the livelihood, therefore, it is imperative to understand the response of agricultural to meteorological drought and the natural influencing mechanisms. In this paper, the Mann-Kendall approach was employed to identify the mutation changes for long-term agricultural and meteorological drought conditions at annual and seasonal time scales Palmer drought severity index (scPDSI) and standard precipitation evapotranspiration index (SPEI) during 1970–2016 in the upper Indus, Kabul and Jhelum River basins. The wavelet coherence is further used to assess the relationship between meteorological and agricultural drought and the large-scale mechanisms. The entire basin exhibited a substantial trend in agricultural drought at annual and seasonal scales, and abrupt changes appeared during 1973, 1983, 1993, 1997, 2003, and 2015. The 2001 drought showed a widespread significant extreme encompassing over 58% of its total area. The response time lag of agricultural drought to meteorological drought exhibits considerable seasonal variation, with quicker responses in winter and autumn and slower responses in summer, largely due to the buffering capacity of soils. The intermittent interannual signals appeared more robust over 8–16 months, whereas a significant coherence cycle of 64–128 months is dominant after mid-90s with IOD, ENSO, SOI, PDO, and NAO in the study area. The findings will help in formulating the future policies related to drought in the country for sustainable natural resources management.